Exploration of oral hygiene practices, oral health status, and related quality of life of individuals residing in the Rorya district of Tanzania, East Africa - Gudsoorkar, Priyanka; Nolan, Rachael; Kafle, Sweta; Dubey, Aayush (Frontiers in Oral Health, 2024)
IntroductionOral health substantially impacts individuals’ quality of life, making it an important target for global health interventions. This research describes oral health status, practices, and beliefs within the Rorya district of Tanzania to understand barriers to care.MethodsTo quantify physical oral health status, intraoral examinations were conducted on adults, noting the Decayed Missing and Filled Teeth (DMFT) and Comprehensive Periodontal Inflammatory Burden Index (CPBI). Oral Health-Related Quality of Life (OHRQoL) and semi-structured interviews were conducted to understand oral hygiene behaviors and beliefs. Data was analyzed via two-sample t-tests, Pearson's statistics, and NVIVO.ResultsA purposive sample (n = 139) of participants self-reported to reside in either Burere (n = 32), Nyambogo (n = 52), or Roche (n = 55) were assessed. A two-sample t-test revealed females (n = 67; x¯ = 7.1; SD = 5.4; p < 0.05) have a significantly higher DMFT score than males (n = 72; x¯ = 3.7; SD = 3.9). Moreover, the OHRQoL score of females (n = 67; x¯ = 12.10; SD = 14; p < 0.05) were significantly higher than males (n = 72; x¯ = 10.16; SD = 3). In contrast, males have significantly higher CPBI scores (x¯ = 3.8; SD = 1.5; p=<0.05) than females (x¯ = 3.0; SD = 1.3). Additionally, older age groups presented higher GI and PISA scores, while the younger group (20–30 years) displayed the highest mean DMFT score. The themes that emerged from semi-structured interviews were “pearls of laughter guarded by wisdom teeth,” “whispered tales of oral tides and communal echoes,” and “tales of the tooth fairy.”DiscussionIn this community, proper oral health maintenance techniques are vital yet frequently disregarded, mainly due to disparities in access to resources, reflected in oral health scores. Addressing this is a crucial intervention, presenting an opportunity to uplift overall well-being. Moreover, gender and age disparities in oral health highlight the urgent need for tailored interventions.